Handbook of medicinal spices - Duke, James A. (CRC Press LLC, 2011)
When the "Father of Medicine" uttered those famous words, spices were as important for medicine, embalming, preserving food, and masking bad odors as they were for more mundane culinary matters. Author James A. Duke predicts that spices such as capsicum, cinnamon, garlic, ginger, onion, and turmeric will assume relatively more medicinal importance again, as the economic costs and knowledge of the side-effects of prescription pharmaceuticals increase. After all, each spice contains thousands of useful phytochemicals. Pharmaceuticals usually contain only one or two.